Desenvolvimento do aplicativo "O Número Secreto" e uma experiência de aplicação para alunos do ensino fundamental - Tagliaferro, Daniel (Universidade Federal de São Carlos, 2023)
The present work has, as its objective, the development of an application of the game “The Secret Number”, available on the OBMEP´s website, and its proposed use in the classroom. Currently, Math teachers face enormous difficulties in teaching various contents, especially topics that require great mental effort from students, since the modern student is a differentiated one who requires new and innovative practices for effective learning. So, the use of games in the classroom is an interesting pedagogical option. The game “The Secret Number” was chosen as it contributes to the development of mathematical logic, the fundamental theorem of counting, and basic notions of probability. The application was developed on the SCRATCH platform and the activity sheets were created using the CANVAS application. Through the application of the game in the classroom, a gradual improvement was observed in the students' strategies to win the game, as well as an increase in their interest in the contents being taught.
Development of the application "The Secret Number" and an application experience for elementary school students
Keywords: Jogos; SCRATCH; Princípio fundamental da contagem; Lógica matemática; Games; SCRATCH; Fundamental couting principle; Mathematical logic; CIENCIAS EXATAS E DA TERRA::MATEMATICA